An ultra-long combined trimmed narrow V-belt and its manufacturing process
By adopting a combined structure of ethylene propylene rubber, fiber-reinforced skeleton material, polyurethane or soft rubber, and nanocoated on the surface, the existing V-band lacks weather resistance in high temperature or harsh environments is solved, and higher durability, tensile strength and transmission efficiency are achieved.
Patent Information
- Application Number
- CN202411667005.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-04
AI Technical Summary
The existing V-bands are insufficient weather resistance in high temperature or harsh environments, have short service life, low tensile strength, are prone to deformation or fracture, high friction coefficient leads to increased energy loss, reduced transmission efficiency and high maintenance costs.
Ethylene propylene rubber is used as the outer layer, fiber-reinforced skeleton material is used as the intermediate layer, polyurethane or soft rubber is used as the inner shock absorbing layer, and nanocoating is carried out on the surface, and nanosilicon dioxide or nanoboronitride is used as the coating material.
It significantly improves the weather resistance and durability of the V-band, enhances the tensile strength and fatigue resistance, reduces the friction coefficient, improves the transmission efficiency, extends the service life and reduces maintenance costs.
Smart Images

Figure CN119755272A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mechanical transmission, in particular to an ultra-long combined trimmed narrow V-belt and a preparation process thereof. Background Art
[0002] At present, ultra-long ganged trimmed narrow V-belts are widely used in high-precision manufacturing equipment, heavy machinery and complex transmission systems. Its main function is to transmit power efficiently through multiple ganged V-belts. However, with the complexity of industrial equipment and the diversification of operating environments, existing V-belts face harsh working conditions, including high temperature, high humidity, chemical corrosion and long-term continuous operation. Therefore, the industry's performance requirements for V-belts are gradually increasing, especially in terms of weather resistance, fatigue resistance and transmission efficiency. The V-belts of existing technologies can no longer fully meet these emerging needs.
[0003] Traditional V-belts are composed of rubber material and fiber skeleton layer. The rubber layer is used to provide flexibility and friction, and the fiber skeleton is used to increase the strength and tensile resistance of the belt body. The manufacturing process of V-belts includes vulcanization molding of rubber and reinforcement and compounding of fiber materials, and mechanical cutting and edge grinding processes to ensure the accuracy of the transmission belt. During the transmission process, the V-belt transmits power through friction with the pulley. Its efficiency depends on the performance of the belt material, manufacturing accuracy and the complexity of the operating environment.
[0004] However, V-belts in the prior art often face the problems of material aging and hardening under high temperature or harsh environment, resulting in insufficient weather resistance, shortened service life, and increased equipment maintenance costs. In addition, the fatigue resistance of traditional fiber-reinforced structures is limited. After being subjected to high loads for a long time, they are prone to breakage or deformation, affecting the stable operation of the equipment. At the same time, the friction coefficient of the surface of the existing V-belts is relatively high, which increases energy loss and reduces transmission efficiency. In addition, due to frequent wear caused by friction, the V-belts need to be replaced regularly during equipment operation, and the maintenance cost remains high. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides an ultra-long combined trimmed narrow V-belt and a preparation process thereof, which solves the problems in the prior art of V-belts such as insufficient weather resistance resulting in short service life, low tensile strength and easy deformation and fracture, and high friction coefficient resulting in increased energy loss.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: an ultra-long combined trimmed narrow V-belt and a preparation process thereof, comprising:
[0007] The outer layer is EPDM rubber, which has a tensile strength of 7-21MPa, a hardness of 50A-70A, and good heat resistance and weather resistance;
[0008] The middle layer is a fiber-reinforced skeleton material, wherein the fiber is aramid fiber or polyester fiber, the elastic modulus of the fiber is 70-130GPa, and the tensile strength is 3000MPa;
[0009] The inner layer is a shock-absorbing layer of polyurethane or soft rubber with a thickness of 1–2 mm;
[0010] The outer surface is treated with a nano-coating of nano-silicon dioxide or nano-boron nitride with a coating thickness of 1–5 μm to reduce the friction coefficient and improve wear resistance.
[0011] Preferably, the EPDM rubber of the outer layer is prepared by the following formula:
[0012] EPDM base rubber: 100 parts;
[0013] Enhancer: 50 parts;
[0014] Vulcanizing agent: 1.5 parts;
[0015] Anti-aging agent: 2 parts;
[0016] Plasticizer: 5 parts.
[0017] Preferably, the skeleton layer fibers are braided in a three-strand or five-strand aramid fiber structure, and the diameter of a single fiber is 0.1-0.3 mm, so as to enhance the tensile and fatigue resistance of the V-belt.
[0018] Preferably, the friction coefficient of the nano coating is 0.1-0.15, and the thickness of the nano coating is determined by the following formula:
[0019]
[0020] Wherein, h is the coating thickness, m is the mass of the nanomaterial in grams, A is the surface area of the coating in square centimeters, and ρ is the density of the material in grams / cubic centimeter. The density of the nano-silicon dioxide is 2.65 g / cm 3 .
[0021] Preferably, the edge trimming of the V-belt is completed by a laser cutting process, with a laser cutting power of 30-50W, a cutting speed of 50-100mm / s, a cutting beam diameter of 0.1mm, and ensuring that the edge roughness Ra value is less than 1.6μm.
[0022] A preparation process for preparing an ultra-long combined trimmed narrow V-belt comprises the following steps:
[0023] Material mixing: Mix the outer layer of EPDM, carbon black, vulcanizer, antioxidant and plasticizer at 90-120°C for 8-15 minutes;
[0024] Extrusion molding: The multi-layer composite material is made into a belt body blank through an extrusion process, with the outer layer being EPDM, the middle being a fiber-reinforced skeleton material, and the inner layer being a shock-absorbing layer;
[0025] Vulcanization: Place the blank in a vulcanization mold and vulcanize it at 120–160°C and 5–10MPa for 30–60 minutes;
[0026] Laser cutting: Use a 30-50W fiber laser cutting machine to cut the edges of the vulcanized belt at a cutting speed of 50-100mm / s;
[0027] Nano coating spraying: Under vacuum conditions, nano silicon dioxide or nano boron nitride is coated on the surface of the V-belt using ion spraying technology, with a coating thickness of 1–5 μm;
[0028] Coating curing: The coating is cured by heat curing at 80–120°C or UV curing for 10–30 minutes.
[0029] Preferably, in the mixing process, the rubber mixture is mixed in an internal mixer at a speed of 60-80 rpm.
[0030] Preferably, the vulcanization time in the vulcanization process is determined according to the belt thickness t by the following formula:
[0031] t s = k × t 1.5
[0032] Among them, t s is the vulcanization time in minutes; k is the process coefficient, with a typical value of 3-5; t is the strip thickness in millimeters.
[0033] Preferably, after the laser cutting process, the V-belt cut edges are air-cooled or water-cooled by a cooling system, and the cooling time is controlled within 1-3 minutes to prevent deformation of the material edges due to heat accumulation.
[0034] Preferably, the nano coating is cured by a UV curing process, the curing time is 10-15 minutes, and the ultraviolet wavelength is 200-400nm.
[0035] The present invention provides an ultra-long combined trimmed narrow V-belt and a manufacturing process thereof.
[0036] Beneficial effects:
[0037] 1. The present invention uses EPDM as the outer layer material of the V-belt, which significantly improves the weather resistance and durability of the V-belt. EPDM has excellent heat resistance, UV resistance and chemical corrosion resistance, which enables the V-belt to work stably for a long time in extreme environments. This not only prolongs the service life of the V-belt in high temperature, high humidity and chemical corrosion environments, but also reduces the frequent replacement and maintenance costs caused by environmental factors.
[0038] 2. The fiber-reinforced material used in the middle layer of the present invention greatly improves the tensile strength and fatigue resistance of the V-belt. The high elastic modulus and strength of the fiber skeleton ensure that the V-belt remains structurally stable under high load conditions, avoiding breakage or deformation due to excessive stretching. This makes the V-belt of the present invention very suitable for heavy equipment and long-term continuous work applications, and enhances the reliability of equipment operation.
[0039] 3. The present invention significantly reduces the friction coefficient of the V-belt by performing nano-coating treatment on the surface of the V-belt, effectively reducing the energy loss in the transmission process. The low-friction coating not only extends the service life of the V-belt and the pulley, but also improves the transmission efficiency and reduces the noise and vibration during equipment operation. The wear resistance of the coating enables the V-belt to have a longer service life when operating at a high frequency and reduces the maintenance frequency. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Please see attached Figure 1 The present invention aims to provide an ultra-long combined trimmed narrow V-belt and its preparation process, and further improves the performance of the V-belt through high-precision cutting and nano-coating treatment, which is suitable for transmission systems in high-load, high-precision manufacturing equipment.
[0043] 1. The specific structure and principle of V-belt:
[0044] 1.1 Outer material: EPDM
[0045] The outer layer is made of EPDM, a rubber material with excellent heat resistance, weather resistance and oxidation resistance. Its key features are:
[0046] Heat resistance: EPDM can work for a long time in high temperature environment and is suitable for operation at working temperatures of 120℃ or even 150℃, making the V-belt less likely to age, harden or become brittle in high temperature environment.
[0047] Weather resistance: EPDM has extremely strong resistance to UV rays, ozone and oxidation, which makes the V-belt of the present invention have a long and stable service life outdoors or in high UV environments.
[0048] Chemical corrosion resistance: EPDM has good tolerance to chemicals such as acids, alkalis, and salts, and is suitable for transmission needs in harsh chemical environments.
[0049] Through formula optimization (see claim 2), the performance of EPDM is further enhanced, the carbon black in the formula increases the strength and wear resistance of the rubber, the vulcanizer and antioxidant ensure the durability of the material, and the plasticizer improves the flexibility of the rubber. Through this combination, the outer layer of the V-belt has high tensile resistance and wear resistance, and can adapt to long-term work under high load.
[0050] Formula part:
[0051] The hardness of EPDM is determined by its tensile strength (T) and elastic modulus (E), as shown in the following formula:
[0052]
[0053] Among them: H is hardness, usually 50A-70A; T is tensile strength, typical value is 7-21MPa; E is elastic modulus, the elastic modulus of EPDM is generally 2-10MPa.
[0054] 1.2 Middle layer material: fiber reinforced skeleton material
[0055] The middle layer adopts a fiber-reinforced structure, which greatly improves the tensile performance of the V-belt by introducing high-strength fibers (such as aramid fibers or polyester fibers). These fibers have high strength and high elastic modulus, allowing the V-belt to operate under high load conditions without deformation or breakage. Typically:
[0056] Aramid fibers (such as Kevlar) have a tensile strength of up to 3000MPa and an elastic modulus of 70-130GPa, which greatly enhances the tensile resistance of the V-belt.
[0057] Polyester fiber provides good anti-fatigue performance and is suitable for long-term continuous working scenarios.
[0058] The present invention adopts a woven structure of multiple fiber strands (see claim 3), such as three-strand or five-strand weaving, to ensure that the middle skeleton layer has good tensile strength and wear resistance in multiple directions. Formula part:
[0059] The fiber tensile performance formula of the middle layer is as follows:
[0060] σ=E·∈
[0061] Where: σ is the tensile stress of the fiber; E is the elastic modulus, which is typically 70–130 GPa for aramid fibers; ∈ is the tensile strain, which is usually designed to be 10%–20%.
[0062] 1.3 Inner layer material: soft polyurethane shock-absorbing layer
[0063] The inner layer material is made of soft polyurethane (PU) or soft rubber, which has good shock absorption effect. This material can effectively absorb the vibration and impact generated during the working process, thereby reducing the noise and equipment wear caused by vibration during the transmission process, and ensuring the stability of the transmission system.
[0064] The thickness of the inner layer is controlled between 1-2 mm, so that it can provide sufficient shock absorption performance without affecting the overall strength and flexibility of the belt.
[0065] 2. High-precision cutting and surface treatment
[0066] 2.1 Laser cutting process
[0067] The V-belt in the present invention uses high-precision laser cutting technology to process its edge (see claim 5). The laser cutting process has the following advantages:
[0068] High precision: Laser cutting can achieve extremely high cutting accuracy, with an error of less than ±0.01mm. The cutting edge is smooth and flat, which reduces the roughness of the V-belt edge and effectively prevents the edge burrs caused by traditional mechanical cutting.
[0069] Reduce stress concentration: By precisely controlling the beam diameter and cutting speed, the smoothness of the cut edge is ensured, and local thermal deformation and stress concentration of the material are avoided.
[0070] Formula part:
[0071] The smoothness (roughness Ra value) of the edge after laser cutting is estimated by the following formula:
[0072]
[0073] Where: Ra is the roughness; y i is the actual height of the edge cutting point; is the average height; n is the number of measurement points during the cutting process.
[0074] This process ensures that the cutting edge roughness Ra value is less than 1.6μm, greatly reducing the energy loss in the transmission process and improving the transmission efficiency.
[0075] 2.2 Nano coating treatment
[0076] In order to further improve the surface performance of the V-belt, the present invention performs nano coating treatment on the surface of the V-belt by plasma spraying or vacuum evaporation process (see claim 4 and claim 6). The nano coating (such as nano silicon dioxide or nano boron nitride) has a low friction coefficient and high wear resistance, which can significantly reduce the friction coefficient of the V-belt and improve its waterproof, oil-proof and anti-fouling capabilities.
[0077] Formula part:
[0078] The nano coating thickness is determined by the following formula:
[0079]
[0080] Where: h is the coating thickness (μm), with a typical value of 1–5 μm; m is the mass of the nanocoating material (g); A is the coverage area of the coating (cm 2 );ρ is the material density, the density of silicon dioxide is 2.65g / cm 3 .
[0081] By precisely controlling the coating thickness and uniformity, the V-belt of the present invention has an extremely low friction coefficient (0.1-0.15) during the transmission process, which significantly improves the transmission efficiency and prolongs the service life of the V-belt.
[0082] 3. Preparation process
[0083] The present invention also provides an efficient V-belt preparation process (see claim 6), including material mixing, extrusion molding, vulcanization, high-precision laser cutting, nano-coating spraying and curing steps. The following is a detailed description of each step:
[0084] 3.1 Material mixing and extrusion molding
[0085] Material mixing: Mix the EPDM base rubber, carbon black, vulcanizer, antioxidant and plasticizer in an internal mixer for 8-15 minutes, and control the temperature at 90-120°C and the speed at 60-80rpm (see claim 7).
[0086] Extrusion molding: The outer layer, middle layer and inner layer materials are compounded through an extruder to form a belt body blank.
[0087] 3.2 Vulcanization
[0088] Vulcanization process: Place the formed blank into the mold for high temperature and high pressure vulcanization at a temperature of 120-160°C and a pressure of 5-10MPa. The vulcanization time is determined by the following formula:
[0089] t s = k × t 1.5
[0090] Where: t s is the vulcanization time (minutes), k is the process factor (typically 3-5), and t is the strip thickness (mm) (see claim 8).
[0091] 3.3 Laser Cutting
[0092] Laser cutting: Use a fiber laser cutting machine with a cutting power of 30-50W, a cutting speed of 50-100mm / s, and a beam diameter of 0.1mm. After cutting, the cutting is cooled by air or water through a cooling system (see claim 9), and the cooling time is 1-3 minutes to ensure the stability of the cutting edge.
[0093] 3.4 Nano coating spraying and curing
[0094] Nano coating spraying: In a vacuum environment, use plasma spraying equipment to evenly coat the nano material on the surface of the V-belt with a coating thickness of 1–5μm.
[0095] Coating curing: Through UV curing or heat curing process (see claim 10), the curing temperature is controlled at 80-120°C and the curing time is 10-30 minutes to ensure the adhesion and durability of the coating.
[0096] Example 1: Ultra-long combined trimmed narrow V-belt with EPDM outer layer, aramid fiber skeleton and nano-SiO2 coating
[0097] Outer material preparation:
[0098] Use EPDM and mix according to the following formula:
[0099] EPDM base rubber: 100 copies
[0100] Carbon black (N550): 50 parts
[0101] Vulcanizing agent: 1.5 parts
[0102] Anti-aging agent: 2 parts
[0103] Plasticizer: 5 parts
[0104] The mixture was kneaded in an internal mixer at 80° C. for 10 minutes and then extruded in an extruder to form an outer layer material with a thickness of 1.5 mm.
[0105] Skeleton layer material:
[0106] It adopts three strands of **Kevlar fiber** braided structure, each fiber has a diameter of 0.2mm, an elastic modulus of 100GPa and a tensile strength of 3000MPa.
[0107] The skeleton material is compounded with the outer layer, and the total thickness of the compound layer is controlled to 2.5 mm through a calendering process.
[0108] Inner shock-absorbing layer:
[0109] Polyurethane (PU) is used, the hardness is controlled at 60A and the thickness is 1mm.
[0110] Vulcanization process:
[0111] The belt composite material is placed in a mold, the vulcanization temperature is 140° C., the pressure is 8 MPa, and the vulcanization time is 40 minutes.
[0112] Laser cutting:
[0113] A fiber laser cutting machine was used with a cutting power of 40W, a cutting speed of 80mm / s, and a beam diameter of 0.1mm, ensuring that the cutting edge roughness was less than 1.6μm.
[0114] Nano coating spraying:
[0115] Nano-silicon dioxide (SiO2) was used for surface coating treatment, the coating thickness was 3 μm, plasma spraying technology was adopted, the spraying pressure was 1.0 MPa, and the temperature was 700°C.
[0116] Coating curing:
[0117] UV curing process, curing time is 15 minutes, ultraviolet wavelength is 250-400nm.
[0118] Example 2: Ultra-long ganged trimmed narrow V-belt with EPDM outer layer, polyester fiber skeleton and nano BN coating
[0119] Outer material preparation:
[0120] The same EPDM formula was used, the mixing temperature was 85°C, the mixing time was 12 minutes, and the extrusion molding thickness was 1.2 mm.
[0121] Skeleton layer material:
[0122] It adopts a three-strand **polyester fiber (PET)** woven structure, with a single fiber diameter of 0.25mm, an elastic modulus of 6GPa, and a tensile strength of 400MPa.
[0123] The middle layer is compounded by calendering process, and the total thickness is controlled to be 2.8mm.
[0124] Inner shock-absorbing layer:
[0125] Use soft rubber (nitrile rubber), the hardness is controlled at 55A and the thickness is 1.5mm.
[0126] Vulcanization process:
[0127] The vulcanization temperature is 130°C, the pressure is 7 MPa, and the vulcanization time is 45 minutes.
[0128] Laser cutting:
[0129] The laser power is 35W, the cutting speed is 70mm / s, and the beam diameter is 0.12mm, ensuring a smooth cut edge with a roughness of less than 1.8μm.
[0130] Nano coating spraying:
[0131] A nano boron nitride (BN) coating was used with a coating thickness of 4 μm, a plasma spraying temperature of 750° C., and a spraying pressure of 0.9 MPa.
[0132] Coating curing:
[0133] Thermal curing process, temperature is 90℃, time is 20 minutes.
[0134] Example 3: Ultra-long combined trimmed narrow V-belt with EPDM outer layer, Kevlar skeleton, and composite nano-SiO2+BN coating
[0135] Outer material preparation:
[0136] Ethylene propylene diene monomer (EPDM) was used, the mixing temperature was 90°C, the mixing time was 10 minutes, and the extrusion molding thickness was 1.3 mm.
[0137] Skeleton layer material:
[0138] It adopts a five-strand **aramid fiber (Kevlar)** woven structure, with a single fiber diameter of 0.18mm, an elastic modulus of 120GPa, and a tensile strength of 3500MPa.
[0139] The middle layer is compounded by calendering process, and the total thickness is controlled at 3.0mm.
[0140] Inner shock-absorbing layer:
[0141] Polyurethane (PU) is used, the hardness is controlled at 58A and the thickness is 1mm.
[0142] Vulcanization process:
[0143] The vulcanization temperature is 150°C, the pressure is 8.5MPa, and the vulcanization time is 35 minutes.
[0144] Laser cutting:
[0145] The laser power is 45W, the cutting speed is 90mm / s, the beam diameter is 0.1mm, and the cutting edge roughness is less than 1.5μm.
[0146] Nano coating spraying:
[0147] A composite nano-coating (SiO2 and BN) was used with a coating thickness of 3 μm, a spraying temperature of 700 °C and a pressure of 1.2 MPa to ensure uniform adhesion of the two coating layers.
[0148] Coating curing:
[0149] UV curing process, curing time is 12 minutes, and the wavelength is controlled at 300-400nm.
[0150] Comparative Example 1: Using ordinary chloroprene rubber (CR) outer layer and mechanical cutting
[0151] Outer material: Neoprene (CR), thickness 1.5mm, no reinforcing agent added.
[0152] Skeleton layer: Use ordinary polyester fiber (PET), single strand weaving, thickness 2mm.
[0153] Inner layer: Nitrile rubber, thickness 1mm.
[0154] Vulcanization process: vulcanization temperature 120℃, pressure 6MPa, vulcanization time 50 minutes.
[0155] Mechanical cutting: Cutting by traditional mechanical tool, edge roughness is 3.5μm, no coating treatment.
[0156] Comparative Example 2: Using ordinary rubber outer layer and mechanical cutting
[0157] Outer material: ordinary rubber, thickness 1.2mm, without any weathering agent added.
[0158] Skeleton layer: single strand Kevlar fiber, diameter 0.3mm, single strand braided, thickness 2mm.
[0159] Inner layer: soft rubber, thickness 1.2mm.
[0160] Vulcanization process: vulcanization temperature 110°C, pressure 5MPa, vulcanization time 55 minutes.
[0161] Mechanical cutting: mechanical tool cutting, edge roughness 3.0μm, no coating treatment.
[0162] Comparative Example 3: Ordinary V-belt with low-strength coating
[0163] Outer material: EPDM, no reinforcement, thickness 1.4mm.
[0164] Frame layer: Use single strand polyester fiber, thickness 2.3mm.
[0165] Inner layer: soft polyurethane, thickness 1.1mm.
[0166] Vulcanization process: vulcanization temperature 120℃, pressure 7MPa, vulcanization time 40 minutes.
[0167] Mechanical cutting: mechanical tool cutting, edge roughness 3.0μm.
[0168] Surface treatment: coated with low-strength polymer coating, thickness 1μm.
[0169] Comparative Experimental Design
[0170] Purpose:
[0171] The performance of V-belts of different embodiments and comparative examples was compared through experiments, and their weather resistance, wear resistance, tensile strength and friction coefficient were evaluated to verify the technical advantages of the V-belts of the present invention.
[0172] Experimental content:
[0173] Wear resistance test: The wear weight (mg) of each V-belt after 1000 revolutions was tested by TABER wear tester.
[0174] Tensile strength test: Use a tensile testing machine to test the breaking strength (MPa) of the V-belt.
[0175] Friction coefficient test: The friction coefficient of the V-belt during operation is measured by a friction tester.
[0176] Weathering test: After the V-belt is exposed to 150°C for 100 hours in a high temperature aging box, its breaking strength change rate is tested.
[0177] Experimental data table.
[0178]
[0179] According to the table, the wear weight of Examples 1, 2, and 3 is significantly lower than that of the comparative example, especially Example 3 has the lowest wear weight under the action of the composite coating, which is only 10 mg, proving the superior wear resistance of the nano coating; the Kevlar fiber reinforced structure in Example 3 makes its tensile strength reach 3500 MPa, which is significantly better than the ordinary fiber structure in the comparative example; the friction coefficients of Examples 1, 2, and 3 are much lower than those of the comparative example, especially the friction coefficient of Example 3 is 0.11, which is 68% lower than that of Comparative Example 1, indicating that the nano coating can effectively reduce transmission friction loss; the strength change rate of Examples 1, 2, and 3 after high-temperature aging is much smaller than that of the comparative example, proving the high weather resistance of the EPDM material, especially Example 3 has only a 4% strength drop, which further verifies the comprehensive effect of the coating and the material.
[0180] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An ultra-long ganged trimmed narrow V-belt, characterized in that: include: The outer layer is EPDM rubber, which has a tensile strength of 7-21MPa, a hardness of 50A-70A, and good heat resistance and weather resistance; The middle layer is a fiber-reinforced skeleton material, wherein the fiber is aramid fiber or polyester fiber, the elastic modulus of the fiber is 70-130GPa, and the tensile strength is 3000MPa; The inner layer is a shock-absorbing layer of polyurethane or soft rubber with a thickness of 1–2 mm; The outer surface is treated with a nano-coating of nano-silicon dioxide or nano-boron nitride with a coating thickness of 1–5 μm to reduce the friction coefficient and improve wear resistance.
2. The ultra-long combined trimmed narrow V-belt according to claim 1, characterized in that: The EPDM rubber of the outer layer is prepared by the following formula: EPDM base rubber: 100 parts; Enhancer: 50 parts; Vulcanizing agent: 1.5 parts; Anti-aging agent: 2 parts; Plasticizer: 5 parts.
3. The ultra-long combined trimmed narrow V-belt according to claim 1, characterized in that: The skeleton layer fibers adopt a three-strand or five-strand aramid fiber braided structure, and the diameter of a single fiber is 0.1-0.3 mm, so as to enhance the tensile and fatigue resistance of the V-belt.
4. The ultra-long combined trimmed narrow V-belt according to claim 1, characterized in that: The friction coefficient of the nano coating is 0.1-0.15, and the thickness of the nano coating is determined by the following formula: Wherein, h is the coating thickness, m is the mass of the nanomaterial in grams, A is the surface area of the coating in square centimeters, and ρ is the density of the material in grams / cubic centimeter. The density of the nano-silicon dioxide is 2.65 g / cm 3 .
5. The ultra-long combined trimmed narrow V-belt according to claim 1, characterized in that: The edge cutting of the V-belt is completed by a laser cutting process, with a laser cutting power of 30-50W, a cutting speed of 50-100mm / s, a cutting beam diameter of 0.1mm, and ensuring that the edge roughness Ra value is less than 1.6μm.
6. A process for preparing an ultra-long combined trimmed narrow V-belt, according to the ultra-long combined trimmed narrow V-belt according to claims 1-5, characterized in that: The following steps are involved: Material mixing: Mix the outer layer of EPDM, carbon black, vulcanizer, antioxidant and plasticizer at 90-120°C for 8-15 minutes; Extrusion molding: The multi-layer composite material is made into a belt body blank through an extrusion process, with the outer layer being EPDM, the middle being a fiber-reinforced skeleton material, and the inner layer being a shock-absorbing layer; Vulcanization: Place the blank in a vulcanization mold and vulcanize it at 120–160°C and 5–10MPa for 30–60 minutes; Laser cutting: Use a 30-50W fiber laser cutting machine to cut the edges of the vulcanized belt at a cutting speed of 50-100mm / s; Nano coating spraying: Under vacuum conditions, nano silicon dioxide or nano boron nitride is coated on the surface of the V-belt using ion spraying technology, with a coating thickness of 1–5 μm; Coating curing: The coating is cured by heat curing at 80–120°C or UV curing for 10–30 minutes.
7. The process for preparing an ultra-long combined trimmed narrow V-belt according to claim 6, characterized in that: In the mixing process, the rubber mixture is mixed in an internal mixer at a speed of 60-80 rpm.
8. The process for preparing an ultra-long combined trimmed narrow V-belt according to claim 6, characterized in that: In the vulcanization process, the vulcanization time is determined according to the belt thickness t by the following formula: t s =k×t 1.5 Among them, t s is the vulcanization time in minutes; k is the process factor, with a typical value of 3-5; t is the strip thickness in millimeters.
9. The process for preparing an ultra-long combined trimmed narrow V-belt according to claim 6, characterized in that: After the laser cutting process, the V-belt cut edge is cooled by air or water through a cooling system, and the cooling time is controlled within 1-3 minutes to prevent the edge of the material from being deformed due to heat accumulation.
10. The process for preparing an ultra-long combined trimmed narrow V-belt according to claim 6, characterized in that: The nano coating is cured by a UV curing process, the curing time is 10-15 minutes, and the ultraviolet wavelength is 200-400nm.